The Extent of Media Coverage and Framing Types in the Celebration of Nations, Nationalities and Peoples Day in Ethiopia: In the Case of Some Selected Newspapers (Global Journal of Human-Social Science, 2017)
The purpose of this study was to examine the extent of media coverage and media framing types of Nations, Nationalities and Peoples Day both in government and private print media outlets from 2010-2014. Three newspapers: namely, the government owned Addis Zemen, and the privately owned Addis Admass and Reporter newspapers have been purposefully selected based on ownership, access and large circulation of newspapers. The study also included newspapers published in November 24 to December 24 from 2010 to 2014. Accordingly, 135 news articles were analyzed by using both quantitative and qualitative methods. Quantitative content analysis and in-depth interview methods were dominantly used. Moreover, in-depth interviews were conducted with 9 key informants from government and private media houses. Accordingly, the findings of the study revealed the dominance of development frame over other media frame types both in Addis Zemen and Reporter Amharic newspapers.
Keywords: media framing; media coverage; positive and negative tone; celebration of nations; nationalities and peoples day; major government events